IMI Prevention of Myopia and Its Progression - Jonas, Jost B.; Ang, Marcus; Cho, Pauline; Guggenheim, Jeremy A.; He, Ming Guang; Jong, Monica; Logan, Nicola S.; Liu, Maria; Morgan, Ian; Ohno-Matsui, Kyoko; Pärssinen, Olavi; Resnikoff, Serge; et al. (Investigative ophthalmology & visual science, 2021)
The prevalence of myopia has markedly increased in East and Southeast Asia, and pathologic consequences of myopia, including myopic maculopathy and high myopia-associated optic neuropathy, are now some of the most common causes of irreversible blindness. Hence, strategies are warranted to reduce the prevalence of myopia and the progression to high myopia because this is the main modifiable risk factor for pathologic myopia. On the basis of published population-based and interventional studies, an important strategy to reduce the development of myopia is encouraging schoolchildren to spend more time outdoors. As compared with other measures, spending more time outdoors is the safest strategy and aligns with other existing health initiatives, such as obesity prevention, by promoting a healthier lifestyle for children and adolescents. Useful clinical measures to reduce or slow the progression of myopia include the daily application of low-dose atropine eye drops, in concentrations ranging between 0.01% and 0.05%, despite the side effects of a slightly reduced amplitude of accommodation, slight mydriasis, and risk of an allergic reaction; multifocal spectacle design; contact lenses that have power profiles that produce peripheral myopic defocus; and orthokeratology using corneal gas-permeable contact lenses that are designed to flatten the central cornea, leading to midperipheral steeping and peripheral myopic defocus, during overnight wear to eliminate daytime myopia. The risk-to-benefit ratio needs to be weighed up for the individual on the basis of their age, health, and lifestyle. The measures listed above are not mutually exclusive and are beginning to be examined in combination.